Numerical Method for Investigation of 1D Processes in Porous Media with Heterogeneous Reactions when Flow Rate of Oxidant Regulates itself; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Lutsenko N. A. (Diagnostics and Engineering of Novel Materials, 2014)
Title screen